Linguopragmatic analysis of numerical component phraseological units in English and Uzbek - Abdusalomova, Mokhigul Zoxidjon qizi (The Lingua Spectrum, 2026)
The study of linguopragmatic analysis of numerical component phraseological units plays one of the most important roles in linguistics. The aim of the study is to analyze the linguopragmatic potential of numerical component phraseological units in English and Uzbek and this study focuses on the phraseological units with numerical components in English and Uzbek. In this study the research methods include comparative, semantic and cognitive, qualitative analysis methods. This study illustrates that phraseological units with numerical components do not merely represent mathematical quantities. They function as powerful carriers of cultural memory, emotional evaluation, and pragmatic intent. The findings highlight linguopragmatic analysis of numerical component phraseological units has significant role in understanding these units in the context and their function. This article delves into the analysis of numerical component phraseological units from a linguopragmatic perspective and it represent how these phraseological units function in the context to evaluate, influence, or evoke emotions in the listener or reader transcending their literal meaning.